ナンキョク ロケット S-210JA-20 21 ニヨル オーロラヒス ノ カンソク e. イベント セッション ダイ 2 カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 木村, 磐根; キムラ, イワネ; 松尾, 敏郎; マツオ, トシロウ; 鎌田, 哲夫; カマタ, テツオ; 長野, 勇; ナガノ, イサム; KIMURA, Iwane; MATSUO, Toshiro; KAMATA, Tetsuo; NAGANO, Isamu (1980)
P(論文) 南極ロケットS-210JA-20,21号機で観測されたオーロラヒスについて述べる.前者は地磁気じょう乱時に発射されたが,後者は静穏時であり,ともにオーロラ中に打ち込まれた.両ロケットで観測されたヒスのスペクトルで電界と磁界の比を求めた結果,このヒスが,ホイスラーモード波であることが判明した.このオーロラヒスのロケットで観測されたポインティング電力と昭和基地上での電力の差は,下部電離層を通過の減衰により定量的に説明がつけられることがわかった.ロケットで観測されたVLF雑音強度の時間変化が,同じロケットで観測された40-60keVの電子および電子密度の変化と比べられたところ,特に20号機の40-60keV電子とオーロラヒスの相関はよいが,21号機はよくないという結果となった. Characteristics of auroral hiss emissions observed in the Antarctic rocket experiments using the S-210JA-20 and 21 rockets are described.The S-210JA-20 rocket was launched in a geomagnetically disturbed condition. whereas the S-210JA-21 was launched in a calm condition, although the both penetrated into auroras. From the ratio of the electric field intensity to the magnetic field intensity, the hiss emissions observed on the above two rockets are identified as the whistler mode. The Poynting fluxes of the auroral hiss observed on the rockets are compared with those observed on the ground and the difference in the flux is found to be ascribed to the attenuation through the lower ionosphere. Time variations of the VLF noise intensity observed on the rockets are compared with those of electron flux of 40-60 keV and electron density simultaneously observed on the same rockets. It is found that the VLF noise level corresponding to the auroral hiss is well correlated with the electron flux in the S-210JA-20 experiment, but the correlation is not good in the S-210JA-21 experiment. departmental bulletin paper